(untitled) (MAUSAM, 1966)
The ground motion of microseisms from the Bay of Bengal was studied with the help of records obtained from the three component seismographs of the Press-Ewing type. The results of the study indicate that the microseisms from the Bay of Bengal consist of 70 per cent Rayleigh waves and 30 per cent Love waves.